Effect of aggregate saturation degree on the freeze–thaw resistance of high performance polypropylene fiber lightweight aggregate concrete. (1st August 2017) - Zhu, Cong; Niu, Jiangang; Li, Jingjun; Wan, Chaojun; Peng, Jiahui
Highlights: Two pre-wetting aggregate methods were adopted: pre-wetted under normal and 1.5 MPa pressure. Effect of aggregate saturation degree on the workability, compressive strength was studied. High aggregate saturation degree had a negative effect on the freeze–thaw resistance. High aggregate saturation degree served to the growth of AFt and CH crystal. Abstract: The aim of this study was to investigate the influence of lightweight aggregate (LWA) saturation degree on such properties of high performance polypropylene fiber lightweight aggregate concrete (HPPLWC) as workability, compressive strength and freeze–thaw resistance. LWAs pre-wetted into four different degrees were used in this experiment. The results showed that: (1) increasing saturation degree of LWA could significantly decrease the slump loss with time of the fresh mixtures; (2) the 28 and 56-day compressive strength of samples with different saturation degree of LWA had no significant variation; (3) the relative dynamic elastic modulus was seriously reduced when the pre-soaked degree of LWA was close to saturation. In addition to SEM investigations of interfacial transition zone (ITZ), it was observed that increasing the amount of LWA water absorption served to the growth of ettringite (AFt) and calcium hydroxide (CH) crystal at 3 d; when cured for 28 d, the variation in saturation degree of LWA had no obvious effect on the ITZ morphology.